Factores para la evaluación por talento y competencias durante el proceso productivo en Iquitos al año 2021 - Menacho Rojas, Hector Anibal (2024)
This research is entitled, “FACTORS FOR THE EVALUATION BY TALENT AND COLLECTIVE COMPETENCES DURING THE PRODUCTIVE PROCESS at IQUITOS by THE YEAR 2021”, having as a problem, public and private companies use factors that evaluate the behavior of the worker individually against the productive process that always is a collective way. The objective is the research is to propose some factors to in order evaluate workers in their collective work and it is justified because it will provide new concepts of factors for the various models of personnel evaluation. This thesis complied with the formal requirements for as scientific research that the National University of the Peruvian Amazon demands with great rigor, being developed it the city of Iquitos in the 2023 under the financing of the sustaining researcher.